Investigation of Brake Pad Wear Effect due to Temperature Generation Influenced by Brake Stepping Count on Different Road Terrains - Rusli, Majuma; Mohamad Heerwan, Peeie; Ondong, Kerisvin; Othman, Abu Hassan (Universitas Muhammadiyah Magelang, 2023)
The use of vehicles in Malaysia has become a need and important to commute to the workplace and commercial business transportation. This necessity resulted in an increase in the number of cars on the road that eventually increase the number of accidents that resulted in the loss of life which is also one of the leading killers in Malaysia. Deriving from this phenomenon, car maintenance especially brake systems has become imperative that eventually become the main objective of this research to investigate the effect of different road terrains to brake pad wear. The experimental vehicle is operated in two different road terrains namely hilly and flat roads and each road terrain is set to complete 1000km of investigation traveled distance. Three main investigation parameters are brake pad thickness wear, the temperature generated from rubbing the brake pad with the rotor, and the brake force applied on the brake pedal. A CANedge external onboard diagnostic (OBD) logger is used to collect real-time data on the relevant parameters from the vehicle’s ECU for analysis. The result from the experiments found that the average brake pad wear rate during hilly roads is 53% higher than that of flat roads. Likewise, brake pad temperature generation on a hilly road is 34% higher than that on a flat road. However, the brake pedal force applied during braking is 60% higher on flat roads compared to on hilly roads. From the findings, data from the vehicle OBD2 and the brake pad wear can be analyzed to provide an electronic signal for indication of timely maintenance for the brake pad.